The Implementation of Merdeka Curriculum in English Subject - Wilson, Stephen; Nurkhamidah, Neni (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2023)
Merdeka Curriculum is a brand-new curriculum that was designed to give the students a fun learning experience, without any stress and pressure to reveal their natural talent in learning. The purpose of Merdeka Curriculum is to create a learning environment without any stress and pressure that the students experience in the learning process. This study will analyze the implementation of Merdeka Curriculum of grade X English subject in SMA Negeri 85 Jakarta Barat. The study method that was used in this study is Qualitative approach by collecting information in the observation process in grade X class while conducting English subject, and interview with the grade X English teacher with the data collection type of “what” and “why” subjectively. The results of data analysis shows that there are challenges in implementing the Merdeka Curriculum in grade X English subject in balancing the differentiation competency levels of students that were too far. The findings imply that teachers need special training in implementing the Merdeka Curriculum to solve the problem that was mentioned